Excess dopant effect in platinum‐based alloys toward the oxygen electroreduction reaction. (13th July 2022) - Kabiraz, Mrinal Kanti; Kim, Hee Jin; Hong, Youngmin; Chang, Qiaowan; Choi, Sang‐Il
Abstract: Doping the PtNi octahedra with trace amount of transition metals has recently been shown to significantly improve the activity and durability of the oxygen reduction reaction (ORR). However, the role of excessive amounts of doped elements on ORR performance is unclear. In this work, PtNi octahedra were synthesized with and without excess Mo dopant. Also, spherical PtNi nanoparticles containing excess Co dopant were synthesized. The ORR performance revealed that PtNiMo octahedra and PtNiCo nanoparticles showed inferior ORR activities compared to bimetallic PtNi octahedra. Based on the electrochemical analysis, we found that unfavorable oxygen‐binding strengths of PtNiMo and PtNiCo catalysts decrease the ORR performances. Abstract : Trace metal dopants are known to promote the oxygen reduction reaction (ORR) performance of PtNi‐based nanocatalyst. In this work, however, we found that excess dopant increases the oxygen‐binding strength at the catalytic site, thereby decreasing ORR performance.